Digital Platform Transformation and Socio-economic Resilience Among Indonesia’s Motorcycle Ride-hailing Drivers - Soulthoni, Hannin Pradita Nur; Upe, Ambo; Mugambiwa, Shingirai; Johar, Siti Sarawati (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
The Fourth Digital Revolution has transformed Indonesia's informal transportation sector, particularly traditional motorcycle taxi drivers transitioning to digital ride-hailing platforms. This shift represents movement from location-bound, passive income generation to algorithm-driven, flexible employment. Despite widespread Grab adoption across secondary cities, limited research examines multidimensional impacts on drivers' socio-economic well-being beyond metropolitan areas. This study investigates how digital transformation affects the income and social well-being of former traditional motorcycle taxi drivers in Kendari City, a representative secondary urban area. The research employed a qualitative exploratory case study design, utilizing in-depth interviews with eight primary informants who transitioned to the Grab platform, supplemented by community leaders and driver representatives. Data collection used methodological triangulation, combining semi-structured interviews, participant observation, and document analysis over three months. Analysis followed Braun and Clarke's thematic framework, integrating Digital Transformation Theory, Platform Economy Theory, and Social Impact Theory. Findings reveal substantial positive impacts across multiple dimensions. Economically, drivers experienced significant income improvements, enhancing financial stability and predictability. Beyond monetary gains, digitalization strengthened social well-being through improved access to children's education and healthcare, greater work-life balance, and enhanced psychological well-being through reduced income uncertainty. However, challenges emerged regarding platform commission fees and technological dependence. Digital transformation through ride-hailing platforms serves as a powerful economic empowerment instrument, significantly improving income security and multidimensional social well-being. The transition constitutes a structural transformation reducing informal sector uncertainties while providing occupational autonomy, offering evidence-based insights for inclusive digital transformation policies.